The Generating Process and an Extension of Jewitt's Location Independent Risk Concept - Landsberger, Michael; Meilijson, Isaac (Management Science, 1994)
A generating process of Jewitt's location independent risk concept is derived in terms of left stretches based on single crossings between distributions. For concave nondecreasing utility functions this stochastic order preserves monotonicity between risk premium and the Arrow-Pratt measure of risk aversion. We show that a stronger order, the Bickel-Lehmann notion of dispersion, preserves this monotonicity for the larger class of nondecreasing utilities.